Recent Advances and Perspectives on the Polymer Electrolytes for Sodium/Potassium‐Ion Batteries. Issue 31 (28th May 2021) - Yin, Hang; Han, Chengjun; Liu, Qirong; Wu, Fayu; Zhang, Fan; Tang, Yongbing
Abstract: Owing to the low cost of sodium/potassium resources and similar electrochemical properties of Na + /K + to Li +, sodium‐ion batteries (SIBs) and potassium‐ion batteries (KIBs) are regarded as promising alternatives to lithium‐ion batteries (LIBs) in large‐scale energy storage field. However, traditional organic liquid electrolytes bestow SIBs/KIBs with serious safety concerns. In contrast, quasi‐/solid‐phase electrolytes including polymer electrolytes (PEs) and inorganic solid electrolytes (ISEs) show great superiority of high safety. However, the poor processibility and relatively low ionic conductivity of Na + and K + ions limit the further practical applications of ISEs. PEs combine some merits of both liquid‐phase electrolytes and ISEs, and present great potentials in next‐generation energy storage systems. Considerable efforts have been devoted to improving their overall properties. Nevertheless, there is still a lack of an in‐depth and comprehensive review to get insights into mechanisms and corresponding design strategies of PEs. Herein, the advantages of different electrolytes, particularly PEs are first minutely reviewed, and the mechanism of PEs for Na + /K + ion transfer is summarized. Then, representative researches and recent progresses of SIBs/KIBs based on PEs are presented. Finally, some suggestions and perspectives are put forward to provide some possible directions for the follow‐up researches. Abstract : Among electrolytes for sodium/potassium‐ion batteries, quasi‐/solid phase polymer electrolytes endow with some comprehensive advantages of high safety, wide voltage window, good thermal stability, appropriate mechanical strength, excellent flexibility, good processibility, etc. Herein, the advance of polymer electrolytes is minutely reviewed, and some suggestions and perspectives are put forward to provide some possible directions for the follow‐up researches.